Up-to-date understanding of overtraining syndrome and overlap with related disorders - Nekisa Haghighat; Todd Stull (Hogrefe AG, 2024)
Abstract: Introduction: The rigorous training regimens of elite athletes are, by nature, emotionally, physically, and mentally demanding. These regimens can result in marked improvements in athletic performance when they incorporate adequate intervals of rest and recovery. Continued training in the absence of adequate recovery progresses to a constellation of symptoms that affect medical and mental health, which is referred to as overtraining syndrome (OTS). Method: A literature review was conducted using PubMed, a database of reference on medical research maintained by the US national Library of Medicine and the National Institute of Health. Search terms included "overtraining syndrome", "Unexplained Underperformance" (UUPS), "Burnout" in athletes. Results: The collection of the published work provides insight into the multidimensional composition and complexity of OTS in athletes. OTS progresses along a continuum without adequate recovery. Conclusion: Decreased athletic performance in the setting of increased training intensity without appropriate recovery, often accompanied by changes in mood, motivation, and general well-being are the distinctive features of OTS. OTS is preceded by stages of underperformance that are reversable and preventable, highlighting the importance of recognizing, managing, and preventing overtraining in athletes in order to prevent long-term negative outcomes is a maladaptive response to an imbalance between exercise and recovery.